1972
DOI: 10.1136/gut.13.2.75
|View full text |Cite
|
Sign up to set email alerts
|

75Se-selenomethionine scanning in the diagnosis of tumours of the pancreas and adjacent viscera: The use of the test and its impact on survival

Abstract: SUMMARYThe results ofpancreatic scanning with 75Se-selenomethionine in 393 carefully documented patients over a two-year period are presented. On follow up 50 patients had operatively proven malignant tumours in the gland and a further 22 had similar tumours in adjacent organs, clinically mimicking carcinoma of the pancreas and in many cases causing scan abnormalities. Five patients had pancreatic adenomata. Remote tumours rarely affected the scan. Examination of the role of scanning in patients with neoplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The in vitro serum stability of all nine 99m Tc(CO) 3 -amino acid complexes was also monitored by thin layer chromatography up to 18 h of incubation at 37 °C. The level of free radioactive species generated in 99m Tc(CO) 3 amino acid complexes of the former series (1-4) after 18 h incubation was around 8% whereas in the rest of the complexes (5)(6)(7)(8)(9) it was between 10 and 12%. The study suggested that the stabilities of the first four 99m Tc(CO) 3 -amino acid complexes (1-4) were better than those of the rest (5)(6)(7)(8)(9).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The in vitro serum stability of all nine 99m Tc(CO) 3 -amino acid complexes was also monitored by thin layer chromatography up to 18 h of incubation at 37 °C. The level of free radioactive species generated in 99m Tc(CO) 3 amino acid complexes of the former series (1-4) after 18 h incubation was around 8% whereas in the rest of the complexes (5)(6)(7)(8)(9) it was between 10 and 12%. The study suggested that the stabilities of the first four 99m Tc(CO) 3 -amino acid complexes (1-4) were better than those of the rest (5)(6)(7)(8)(9).…”
Section: Resultsmentioning
confidence: 93%
“…4,5 In late seventies 75 Se-selenomethionine was tested for the detection of pancreatic carcinoma, however the poor imaging quality of the radiotracer made the compound unattractive. 6 The discovery of the superior physical properties of 99m Tc led to the incorporation of this radionuclide in organic compounds through chelation for scintigraphic imaging studies. 7 99m Tcglycine was the first technetium labeled amino acid developed in 1964 with the hope that it would exhibit pancreatic uptake like selenomethionine.…”
Section: Introductionmentioning
confidence: 99%
“…However, only 18 of the 33 patients with a normal pancreas had a normal scan. Other workers McCready and Cottrall, 1971;McCarthy et al, 1972;Agnew et al, 1973) have pointed out that non-pancreatic conditions could cause abnormalities in scanning, including postgastrectomy/vagotomy, peptic ulceration, metastatic disease, cirrhosis, and diabetes mellitus. Many patients with a normal pancreas studied in this series had one of the above conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients with a normal pancreas studied in this series had one of the above conditions. Thus while a normal scan argues strongly against the presence of pancreatic disease, an abnormal scan may be misleading McCarthy and Brown, 1969;McCarthy et al, 1972;Braganza et al, 1973;Youngs et al, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all but two of the 17 patients with abnormal scans in this control group had normal exocrine function assessed by the secretin-pancreozymin test. McCarthy, Brown, Melmed, Agnew, and Bouchier (1972) list 32 conditions with a high incidence of abnormal scans in which the appearance does not reliably reflect pancreatic morphology or function. These cover many common clinical conditions including diabetes mellitus and peptic ulcer.…”
Section: Discussionmentioning
confidence: 99%